Separating the influence of temperature, drought, and fire on interannual variability in atmospheric CO2. Issue 11 (19th November 2014) - Keppel‐Aleks, Gretchen; Wolf, Aaron S.; Mu, Mingquan; Doney, Scott C.; Morton, Douglas C.; Kasibhatla, Prasad S.; Miller, John B.; Dlugokencky, Edward J.; Randerson, James T.
Abstract The response of the carbon cycle in prognostic Earth system models (ESMs) contributes significant uncertainty to projections of global climate change. Quantifying contributions of known drivers of interannual variability in the growth rate of atmospheric carbon dioxide (CO2) is important for improving the representation of terrestrial ecosystem processes in these ESMs. Several recent studies have identified the temperature dependence of tropical net ecosystem exchange (NEE) as a primary driver of this variability by analyzing a single, globally averaged time series of CO2 anomalies. Here we examined how the temporal evolution of CO2 in different latitude bands may be used to separate contributions from temperature stress, drought stress, and fire emissions to CO2 variability. We developed atmospheric CO2 patterns from each of these mechanisms during 1997–2011 using an atmospheric transport model. NEE responses to temperature, NEE responses to drought, and fire emissions all contributed significantly to CO2 variability in each latitude band, suggesting that no single mechanism was the dominant driver. We found that the sum of drought and fire contributions to CO2 variability exceeded direct NEE responses to temperature in both the Northern and Southern Hemispheres. Additional sensitivity tests revealed that these contributions are masked by temporal and spatial smoothing of CO2 observations. Accounting for fires, the sensitivity of tropical NEE to temperature stress decreased by 25% to 2.9 ± 0.4 Pg C yr−1 K−1. These results underscore the need for accurate attribution of the drivers of CO2 variability prior to using contemporary observations to constrain long‐term ESM responses.